2020
DOI: 10.9734/ajraf/2020/v5i430091
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-sowing Treatments on the Germination of Prosopis africana (Guill. and Perr.) Taub. Seeds

Abstract: Aims: The application of pre-sowing treatment has greatly improved the germination of seeds of tree species used in afforestation programmes all over the world. This study aimed to determine the effect of different pre-sowing treatments on the germination of Prosopis africana seeds. Study Design: The experiment was laid in a completely randomized design. Place and Duration of Study: This study was carried out from 11th November to 30th December 2019atthe Department of Forestry and Wildlife, Faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…These negative correlation trends are expected and suggested that tall and slender tree with small diameter has lower crown ratio values. Similar pattern was observed by previous researchers (Chukwu et al 2018)…”
Section: Correlation Among Tree Growth Variables For Individual Domin...supporting
confidence: 93%
“…These negative correlation trends are expected and suggested that tall and slender tree with small diameter has lower crown ratio values. Similar pattern was observed by previous researchers (Chukwu et al 2018)…”
Section: Correlation Among Tree Growth Variables For Individual Domin...supporting
confidence: 93%
“…Atriplex canescens (Nosrati et al, 2008), Tamarindus indica L. (Muhammad and Amusa, 2003). Treating seeds with acid removes waxy layer by chemical decomposition of the components of seed coat (Dachung and Verinumbe, 2006). H 2 SO 4 disrupts the seed coat and thus lumens of the macro-sclereids get exposed and allows the imbibition of water which triggers protein synthesis and encourages the germination (Jackson, 1994).…”
Section: Discussionmentioning
confidence: 99%